Isolasi dan Identifikasi Bakteri Fiksasi Nitrogen Dari Akar Padi Hidroponik Dan Akar Padi Konvensional - Pinkhan Aliffia Sekar Andini; Kartika Manalu; Rizki Amelia Nasution (Universitas Nusantara PGRI Kediri, 2024)
Nitrogen fixation bacteria are bacteriathat are able to convert free nitrogen into nitrogen that can be used by theplants. This study aims to determine the presence of bacteria fixationnitrogen fixation bacteria in hydroponic and conventional rice roots and can identify the bacteriaidentify the bacteria. Isolation was done from the roots of rice (Oryza sativa) with the scatter blot method on NA (Nutriet Agar), and then tested for thethen tested for the ability to fix nitrogen using mineral-free nitrogen media added with Brontomimineral-free nitrogen medium added with Brontomiul Blue and glucose, which was incubated for 24 hours, thenincubated for 24 hours and then biochemical tests. From the results of the isolation there are 2 isolates that are able to bind nitrogen and have the ability ofHOS 833 ppm and KOS 1,128 ppm. The results of the characteristics and biochemistrycharacteristics and biochemistry showed that the isolate HOS is the genusBacillus genus and KOS is Azotobacter genus.